The genetic regulation and subcellular dynamics of secretory and endolysosomal organelles of Drosophila secondary cells. - Kroeger, B (2017)
Secretory processes underpin the emergence of cellular diversity in complex multicellular organisms. However, our understanding of the basic mechanisms controlling the different secretory and endosomal compartments involved remains surprisingly incomplete. During my DPhil I have studied a specialised epithelial cell type in the male Drosophila accessory glands, the secondary cell, which contains unusually large intracellular compartments that are accessible to detailed morphological study. I characterise the organisation, ultrastructure and molecular composition of this cell’s secretory and endosomal compartments, and I employ specific Rab GTPases, conserved coordinators of membrane trafficking and identity, to define multiple compartmental subtypes. By developing super-resolution and time-lapse microscopy approaches in these cells, I show that numerous intraluminal vesicles (ILVs) are formed within Rab11-labelled secretory compartments and released into the accessory gland lumen as exosomes, the first clear demonstration in eukaryotic cells of exosome biogenesis within a non-late endosomal compartment. Biogenesis of these ILVs is dependent on evolutionarily conserved Endosomal Sorting Complexes Required for Transport (ESCRT) 0-III genes and involves loading of compartment-specific cargoes. Work by others, some in collaboration with me, has shown that these novel mechanisms are conserved in human cells. I show that dense-core granules, the structures employed to package proteins and other molecules destined for regulated secretion, form within large non-cored Rab6- positive compartments, in a process that seems to involve inputs from both the Golgi and recycling endosomal pathways. Further analysis has revealed roles for specific Rabs, for ILVs, and for the conserved fibrillar protein Mfas/TGFBI in different aspects of DCG formation. I also show that DCGs are not only secreted, but can also be degraded by fusion to acidic endosomal compartments. Remarkably, there is evidence that mammalian cells may employ all of these mechanisms and defects in these processes may be linked to diseases like cancer, diabetes and neurodegenerative disorders. Hence my work has established a new system to study complex secretory mechanisms, which can now be developed to model specific disease processes in the future. In summary, I have discovered several novel cell biological mechanisms controlling exosome biology, dense-core granule biogenesis, regulated secretion, and endolysosomal trafficking. Some of these already appear relevant to human health and disease, suggesting that the secondary cell system has considerable further potential for unravelling the fundamental processes underlying eukaryotic secretion in the future.